The academic's handbook - DeNeef, A. Leigh; Goodwin, Craufurd D., 1934-2017 (e-Duke books scholarly collection., 2007)
Revised and expanded, this new edition of the popular Academic's Handbook is an essential guide for those planning or beginning an academic career.